Budgetary Participation and Managerial Performance in Public Sector Organisations: A Study from Nigeria - Babajide OYEWO; Gbadegesin ADEYEYE (Annals of Spiru Haret University Economic Series, 2018)
This study investigated the impact of budgetary participation on managerial performance in public-sector organisations in Nigeria. Questionnaire was used to obtain the opinion of 174 managers (unit and departmental heads) in five public-sector organisations located in Abuja, Nigeria Federal Capital. Results from statistical analysis (descriptive, factor analysis, Kruskal-Wallis tests, correlation and regression) show that there is high level of budgetary participation by managers in public-sector organisations in Nigeria.  Although budgetary participation was observed to positively and significantly impact on managerial functions such as planning, investigating, co-ordinating, supervising, evaluating, and staffing, it exerts the most on planning. The impact of budgetary participation on managerial performance appears to be moderate. Whilst it is desirable for public-sector organisations to adopt sophisticated budgeting techniques, the study advocates for employees’ motivation and deeper involvement in budget matters as a way out of the traditional budgeting quagmire that public-sector organisations are characteristically bedevilled with.